Brassinosteroids in plant developmental biology and stress tolerance - Ahammed, Golam Jalal; Sharma, Anket; Yu, Jingquan; Efimova, Marina V.; Bakshi, Palak; Bali, Aditi Shreeya (Elsevier, Academic Press, 2022)
Modern crop production uses a large suite of agricultural agents that increases plant productivity both under optimal growth and stress conditions. Most of these agents are of artificial origin; many of them are toxic and are pollutants of agricultural production and the environment. One of the ways to solve this problem is to replace traditional agricultural agents with environmentally friendly substances, such as brassinosteroids (BRs), which regulate natural mechanisms of plant growth and development. Currently, more than 70 representatives of this class of hormones are identified in plants of many taxonomic groups. Brassinosteroids have a number of unique properties, including the ability to increase productivity and plant resistance to biotic and abiotic stressors in extremely low concentrations. The steroid hormones used in agriculture are chemically synthesized. Currently, different brassinosteroid species, including chimeric molecules of brassinosteroids with other biologically active compounds, are used on plants for food, drug, and technical purposes.